Lab Scale Production of Mycophenolic Acid on Solid- phase Culture by Standard Strains of Penicillium Brevicompactum - M Afshari; Z Mottaghiyan; A Emamgholi; M Bagheripour; A Zand; M Salehi; M Riazipour; R Kachuei; R Golmohammadi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2012)
Introduction: Mycophenolic acid(MPA), a fungal mycotoxin, is produced by Penicillium brevicompactum and is used for the synthesis of immunosuppressive drugs in pharmaceutical industries. The present study was conducted to evaluate the possibility of mycophenolic acid(MPA) production by standard strains of P. brevicompactum at laboratory level. Methods: Three strains of P. brevicompactum were provided from microbial culture collections. To stimulate MPA production, barley was used as culture medium, and dry heat, wet heat, and gamma radiation were used to sterilize the culture medium. Samples were taken from the culture medium at different intervals, and their MPA level was assessed by HPLC method. Results: P. brevicompactum strain which was prepared from Finland(VTT D-061157) was able to produce MPA more than two other strains(from Germany and Iran). The amount of MPA enhanced linearly until day 10, and after that became relatively constant. Gamma radiation was a suitable method to sterilize the substrate, and nylon bags were evaluated as an easy and cheap container for growing the fungus. Conclusion: Production of MPA with simple and cheap culture media to provide primary substance for immunosuppressive drugs such as mycophenolate mofetile and sodium mycophenolate would be possible.